Stochastic premarshalling of block stacking warehouses. (July 2021) - Maniezzo, Vittorio; Boschetti, Marco A.; Gutjahr, Walter J.
Abstract: Warehouse premarshalling (also pre-marshalling or remarshalling) is the activity of reordering items in a storage location so that subsequent retrieval orders can be serviced with little or no need for further relocations. It has deep impact on warehouse efficiency. We are interested in a stochastic case, where pickup orders become known only at the moment when they are to be retrieved. The problem is framed in a business analytics settings, where a forecasting statistical model based on historic data generates the input of a two stage stochastic optimization module. Computational results both on artificial and real-world data confirm the effectiveness of the approach.